Left atrial enlargement in young high-level endurance athletes - Another sign of athlete`s heart? - Krol, W.; Jedrzejewska, I.; Konopka, M.; Burkhard-Jagodzinska, K.; Klusiewicz, A.; Pokrywka, A.; Chwalbinska, J.; Sitkowski, D.; Dluzniewski, M.; Mamcarz, A.; Braksator, W. (Journal of Human Kinetics, 2016)
Enlargement of the left atrium is perceived as a part of athlete`s heart syndrome, despite the lack of evidence. So far, left atrial size has not been assessed in the context of exercise capacity. The hypothesis of the present study was that LA enlargement in athletes was physiological and fitness-related condition. In addition, we tried to assess the feasibility and normal values of left atrial strain parameters and their relationship with other signs of athlete`s heart. The study group consisted of 114 international-level rowers (17.5 ± 1.5 years old; 46.5% women). All participants underwent a cardio-pulmonary exercise test and resting transthoracic echocardiography. Beside standard echocardiographic measurements, two dimensional speckle tracking echocardiography was used to assess average peak atrial longitudinal strain, peak atrial contraction strain and early left atrial diastolic longitudinal strain. Mild, moderate and severe left atrial enlargement was present in 27.2°%, 11.4% and 4.4% athletes, respectively. There were no significant differences between subgroups with different range of left atrial enlargement in any of echocardiographic parameters of the left ventricle diastolic function, filling pressure or hypertrophy. A significant correlation was found between the left atrial volume index and maximal aerobic capacity (R > 0.3; p < 0.001). Left atrial strain parameters were independent of atrial size, left ventricle hypertrophy and left ventricle filling pressure. Decreased peak atrial longitudinal strain was observed in 4 individuals (3.5%). We concluded that LA enlargement was common in healthy, young athletes participating in endurance sport disciplines with a high level of static exertion and was strictly correlated with exercise capacity, therefore, could be perceived as another sign of athlete`s heart.